The effects of the SNAPPS model on clinical learning experiences for Physician Assistant students (Journal of Applied Learning and Teaching, 2023)
The current study was created to pilot an approach to clinical experiential learning for Physician Assistant (PA) students by teaching students the six-step clinical teaching model: (1) Summarize the case, (2) Narrow the differential diagnosis, (3) Analyze the differential diagnosis (what key patient findings support or lack support for each), (4) Probe the preceptor (ask for clarification of topics about which the learner feels unsure), (5) Plan management (with preceptor input) and (6) Select a care-related issue for self-directed learning; abbreviated to SNAPPS. SNAPPS is known to be learner-led and has been shown in research to be effective in increasing insights into clinical reasoning and encouraging timely feedback to medical students. The research question asked what effect SNAPPS training may have on PA student ratings of (1) learning climate, (2) control of session, (3) communication of goals, (4) promotion of understanding and retention, (5) evaluation, (6) feedback and (7) global assessment on a survey instrument following clinical learning experience. In a Solomon-four group design, PA students from an Atlanta-based PA program completed the validated PA Clinical Rotation Evaluation (PACRE) instrument before and/or after a SNAPPS training or case-based education module. An analysis of variance showed the effects of group designation on the domains of Control of Session (F(3, 9) = 9.084, p= .004), Communication (F(3, 9) = 7.527, p=.008) and Evaluation (F(3, 9) = 5.626, p= .019) was statistically significant for differences in PACRE scores. It was noted that the case-based groups scored clinical rotation higher on the instrument than the SNAPPS groups, highlighting the potential effect that SNAPPS groups may have reflected more critically on their learning experience.